The Effect of Employee Relations and Transformational Leadership on Job Satisfaction: The Mediating Role of Interpersonal Trust in Colleagues and Managers - Atmaja, Dodi Ria; Amanda Putri, Wulan (Journal of Business and Behavioural Entrepreneurship, 2024)
Workplace diversity requires effective management to build positive Employee Relations, which impacts Job Satisfaction and Mental Health of employees. This study explores the influence of Human Resources on Employee Relations, Job Satisfaction, Interpersonal Trust in Managers, and Interpersonal Trust in Colleagues, with mediation by Perceived Value and Employee Satisfaction. The purposive sampling method was used by distributing online questionnaires to employees of fintech companies in Jakarta. Data analysis was performed using PLS-SEM. The results indicate that Employee Relations significantly positively affect Interpersonal Trust in Colleagues and Job Satisfaction. Interpersonal Trust in Colleagues mediates the positive impact of Employee Relations on Job Satisfaction, while Interpersonal Trust in Managers does not show a positive effect on Job Satisfaction. This study contributes to the understanding of employee dynamics in the fintech industry. Future research is recommended to expand the scope of variables such as working conditions, salary, and organizational culture, and to use more anonymous data collection methods to reduce bias. Additionally, disseminating the research beyond Jakarta will provide a broader and more representative perspective from various locations.